“SURVEY ON SPORTS ACHIEVEMENTS IN FOOTBALL, KABADDI, AND KHO-KHO IN THE SCHOOL OF MORADABAD COMMISSIONARY” (Conferencea, 2024)
The study aimed to survey the Sports Achievements of Football, Kabaddi, and Kho-Kho in the schools of Moradabad Commissionary. In this regard, the researcher surveyed 30 senior secondary level schools of the U.P. board, under the radius of Moradabad Commissionary. The random sampling method was used to select the schools for data collection. Copies of the survey scale with covering letters were given to the school principal/physical education teacher, requesting that they give correct and accurate answers and return them as soon as possible. As per the objectives of the study, the Percentage method was used to assess and analyze the data.